Determinan Anemia Pada Ibu Hamil: Literatur Review - Saida, Saida (NHM PRESS, 2024)
Pregnancy-related anemia is a global health issue that can have serious implications for both maternal and fetal health. Anemia during pregnancy is caused by various factors, including iron, folate, and vitamin B12 deficiencies, as well as underlying socioeconomic conditions and infections. The high prevalence of anemia, particularly in developing countries, requires serious attention in efforts to prevent and manage anemia in pregnant women. This literature review was conducted by identifying and analyzing relevant articles on the prevalence, risk factors, management, and impact of anemia during pregnancy. Articles were searched in databases such as PubMed, Google Scholar, and Scopus, using keywords like